Hukum Agraria Berdasarkan Kearifan Lokal Pulau-Pulau Kecil Perbatasan dan Hukum Lingkungan Hidup Wilayah Pulau-Pulau Kecil Perbatasan - Wattimena, Ricky Marthen; Uktolseja, Novyta; Mantayborbir, Rocky S; Kesaulya, Clara (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Ownership rights to land as a type of property right are very important for the state, nation, and people of Indonesia as an agrarian society which is developing towards industrial development and so on, but land is the basic life for humans. Various existing governance concepts, its validity as a basis for agrarian management must be tested again. With these actions, it is hoped that there will be synergy between agrarian issues and an environmentally based management orientation. The aim of the service is to provide legal understanding related to agrarian law based on local wisdom and environmental law in small island border areas. The Service Method is carried out in a lecture by each presenter, the presenter is given time to present the material, after that the participants are invited to ask problems or questions which are then answered in turn by the presenters according to the problem being asked. The results of this community service activity are one form of tridharma activity for educators to play a role in resolving problems that occur in the community, especially regarding Agrarian Law Based on Local Wisdom and Environmental Law on Small Border Islands through legal counseling that discusses the customary rights of customary law communities. encounters development, resulting in changes in the community's living environment.